Marie Laurencin: The Modern Portraits of the Brontës. (3rd April 2023) - Choe, Jian
Abstract: This article examines Marie Laurencin's illustrations for Les Soeurs Brontë: Filles du Vent, René Crevel's booklet of 1930. In five colour lithographs, she brought up to date Brontë portraiture, re-envisioning the sisters as icons of modern urban femininity. The print set can be considered Laurencin's pictorial narratives on the sisters. It signifies the artist's revisionist approach to the myth of the Brontës as elemental Romantic geniuses in rural Yorkshire. Laurencin's exquisite, peculiarly feminized rendition of the sisters displaces them from their usual cult status, alluding to their potential interests and aspirations as ordinary women at a quotidian level. The evanescent, pastel-tinted images unsettle prevailing perceptions of the sisters, evoking the fundamental contingencies of the Brontë iconography. This body of graphic works claims a unique niche within the Brontë portrait canon.